How do central banks write? : an evaluation of inflation-targeting central banks - Fracasso, Andrea; Genberg, Hans.; Wyplosz, Charles; Centre for Economic Policy Research (Great Britain); International Center for Monetary and Banking Studies (London : Centre for Economic Policy Research, 2003)
This study, the second "Special Report" in the ICMB/CEPR series of Geneva Reports on the World Economy, offers the first in-depth analysis and evaluation of 20 inflation reports.
Also produced by International Center for Monetary and Banking Studies, Switzerland.
Includes bibliographical references.
oif 13/02/15, opc 16/12/16
Loan.
Keywords: Banks and banking, Central; Inflation (Finance).